2004
DOI: 10.1103/physrevlett.93.233903
|View full text |Cite|
|
Sign up to set email alerts
|

Stopping Light in a Waveguide with an All-Optical Analog of Electromagnetically Induced Transparency

Abstract: We introduce a new all-optical mechanism that can compress the bandwidth of light pulses to absolute zero, and bring them to a complete stop. The mechanism can be realized in a system consisting of a waveguide side coupled to tunable resonators, which generates a photonic band structure that represents a classical analogue of the electromagnetically induced transparency. The same system can also achieve a time-reversal operation. We demonstrate the operation of such a system by finite-difference time-domain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
184
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(187 citation statements)
references
References 23 publications
(31 reference statements)
3
184
0
Order By: Relevance
“…In 2004, Yanik et al proposed to dynamically modulate the refractive index to generate arbitrarily small group velocity for any light pulse with a given bandwidth. Using coupled cavity arrays [51] or waveguide-coupled cavity system [32], they showed that light pulses can be finally stopped and stored coherently with an all-optical adiabatic and reversible pulse bandwidth compression process ( Figure 17A and B). In 2007, Xu et al [38] reported the demonstration of light storage using fast electro-optical tuning of the resonator refractive index, with storage times longer than the bandwidth-determined photon lifetime of the static device.…”
Section: Light Delay and Storagementioning
confidence: 99%
“…In 2004, Yanik et al proposed to dynamically modulate the refractive index to generate arbitrarily small group velocity for any light pulse with a given bandwidth. Using coupled cavity arrays [51] or waveguide-coupled cavity system [32], they showed that light pulses can be finally stopped and stored coherently with an all-optical adiabatic and reversible pulse bandwidth compression process ( Figure 17A and B). In 2007, Xu et al [38] reported the demonstration of light storage using fast electro-optical tuning of the resonator refractive index, with storage times longer than the bandwidth-determined photon lifetime of the static device.…”
Section: Light Delay and Storagementioning
confidence: 99%
“…This limitation was soon resolved by mimicking the EIT effect in classical oscillator systems [7] that have more merits than in the atomic systems. Recently, various resonant dielectric optical systems including coupled silicon-ring resonators system, photonic crystals, drop-filter cavity-waveguide systems, and a hybridized plasmonic-waveguide system have been proposed and demonstrated to display EIT-like spectral response at room temperature [8][9][10][11][12][13][14][15][16]. These realizations have further catalyzed an ongoing search for classical systems mimicking EIT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our solid-state implementation has an achievable bandwidth of 50 ∌ MHz in contrast to less than 100 kHz in atomic systems, although the delay-bandwidth product is comparable. To obtain longer photon storage, one can consider dynamical tuning (Yanik et al, 2004;Xu et al, 2007;Yanik & Fan, 2007) to tune the cavity resonances with respect to the QD dipolar transitions to break the delay-bandwidth product in a solid-state cavity-QD array system.…”
Section: Spectral Character Of Coupled Cavity-qd Arraysmentioning
confidence: 99%